Hypertension-mediated Cardiac Damage Among Romanian Adult Hypertensive Patients: A Post-hoc Echocardiographic Analysis of the SEPHAR IV Epidemiological Survey - Vîjîiac Aura; Cojocaru Cosmin; Gheorghe-Fronea Oana; Parepa Irinel; Pop Călin; Benedek Theodora; Darabont Roxana; Stănciulescu Diana; Stănciulescu Laura; Branea Ioana Antonia; Vizitiu Anamaria; Itu Lucian Mihai; et al. (Sciendo, 2023)
Background: Data regarding cardiac damage in Romanian hypertensive adults are scarce. Our aim was to assess hypertension-mediated subclinical and clinical cardiac damage using a post-hoc echocardiographic analysis of a national epidemiological survey.